Principles and Strategies for Providing Complementary Foods to Infants and Children Aged 6-23 Months: Ines Ratni Pravitasari, Sonya Hayu Indraswari - Pravitasari, Ines; Hayu Indraswari, Sonya (Jurnal Kedokteran Universitas Lampung, 2025)
Providing complementary foods (MPASI) is the provision of additional food when breast milk or formula milk alone is no longer sufficient to meet nutritional needs. Infants and toddlers who are in the growth and development period require sufficient and varied nutritional intake to optimize their growth and development. This period is very important for children to accept healthy food and drinks and to implement long-term eating patterns. Inadequate nutrition in the early stages of life will result in growth faltering so that children become shorter than the normal size of children their age. Providing appropriate complementary foods is very important because it can have an impact on various aspects of a child's life.